2019
DOI: 10.1017/cjn.2019.316
|View full text |Cite
|
Sign up to set email alerts
|

Migraine with Aura as a Stroke Mimic

Abstract: ABSTRACT:Migraine with aura is one of the causes of stroke mimics. We retrospectively reviewed the 10-year medical records of patients who were treated with acute stroke management protocol. We analyzed the frequency and characteristics of patients with a final diagnosis of migraine with aura. Among the 1355 patients with stroke mimics, migraine with aura was the final diagnosis in 36 patients (2.7%). The most common auras included sensory and brainstem auras followed by motor, visual, and speech/language aura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
1
10
0
2
Order By: Relevance
“…Only half of the patients ful lled IHS criteria previous to admission. Like in previous studies [5,20], we found a higher prevalence of sensory symptoms, mainly negative like numbness, making it hard to distinguish from a thalamic stroke. Although visual aura is the most frequent in MA [4], it is not the most common in cases that raise stroke suspicion.…”
Section: Discussionsupporting
confidence: 74%
“…Only half of the patients ful lled IHS criteria previous to admission. Like in previous studies [5,20], we found a higher prevalence of sensory symptoms, mainly negative like numbness, making it hard to distinguish from a thalamic stroke. Although visual aura is the most frequent in MA [4], it is not the most common in cases that raise stroke suspicion.…”
Section: Discussionsupporting
confidence: 74%
“…When symptoms are prolonged, suspect hemiplegic migraine. Imaging, including DWI-MRI, is normal [80].…”
Section: Migraine Presentationmentioning
confidence: 99%
“…Individuals with migraine report changes in speech during migraine attacks and several studies have documented speech difficulty during the aura phase of the attack as well as prior to and during the attack [1][2][3]. Although severe alterations in speech are easily observed, objective methods for assessing subtle changes in speech production in subjects with headache remain sparse.…”
Section: Introductionmentioning
confidence: 99%